Multiple Casual Sex Scripts: Shared Beliefs about Behavior among Portuguese Emerging Adults - Luz, Rita (2023)
Objective: Empirical research to differentiate casual sex scripts is still limited. We aimed to ascertain the sexual scripts for three main types of casual sexual relationships: hookup, friends with benefits and one-night stands. Methods: Through a mixed-method approach, we performed a study consisting in two sequential tasks to (1) complete three lists of script actions, and (2) identify the most agreed-upon actions for each casual sexual relationship. Results: An important number of actions and events were identified for the three casual sexual scripts, reflecting a high level of elaboration and structure. Following a cognitive-script methodology, the actions retained for the content of the script for each casual sexual relationship were those obtaining at least 60% in respect to the mean of their centrality to the encounter. Only 16.5% of actions were shared among the three scripts, demonstrating their distinctiveness. Conclusion: Knowledge about the different casual sex scripts can be used to develop relational and personal skills within CSRs and decrease unwanted experiences such as condomless sex.